2004
DOI: 10.1111/j.0300-9475.2004.01465.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin Receptor Defects in NOD Mouse Leucocytes: Possible Consequences for Type 1 Diabetes

Abstract: Integrins of the very late antigen (VLA) family mediate leucocyte traffic to lymphoid organs under physiological conditions and in chronic inflammatory situations such as autoimmunity. Accordingly, the current thinking is of a positive correlation between VLA expression and capability of the generation of autoimmunity. Herein we discuss recent findings on the defective expression of integrin-type fibronectin receptors a4b1 (VLA-4) and a5b1 (VLA-5) in the non-obese diabetic (NOD) mouse, a murine model of autoim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…We thus evaluated NOD thymocyte migration toward these stimuli. We previously showed that thymocytes from 8-to 10-wk-old NOD mice migrate less than thymocytes from BALB/c and C57BL/6 mice toward fibronectin, an alteration related to the VLA-5 expression defect (9,10). This was confirmed herein in older 12-to 15-wk-old animals (Fig.…”
Section: Altered Thymocyte Migration In Nod Micesupporting
confidence: 79%
See 1 more Smart Citation
“…We thus evaluated NOD thymocyte migration toward these stimuli. We previously showed that thymocytes from 8-to 10-wk-old NOD mice migrate less than thymocytes from BALB/c and C57BL/6 mice toward fibronectin, an alteration related to the VLA-5 expression defect (9,10). This was confirmed herein in older 12-to 15-wk-old animals (Fig.…”
Section: Altered Thymocyte Migration In Nod Micesupporting
confidence: 79%
“…Accordingly, NOD thymocytes present a defect in the membrane expression of VLA-5 (the ␣ 5 ␤ 1 integrin or CD49e/ CD29, a fibronectin receptor), being first observed in late CD4 Ϫ CD8 Ϫ double-negative cells and more pronounced in mature CD4 and CD8 single-positive subsets. Importantly, NOD thymocyte adhesion to thymic epithelial cells or to fibronectin is diminished; the fibronectin-driven migration of NOD thymocytes is significantly impaired and the giant PVS are filled with VLA-5-negative thymocytes that accumulate in these areas (9,10). Rather surprisingly, however, intrathymic FITC injection, which allows the identification of FITC-stained recent thymic emigrants in peripheral lymphoid organs, showed similar rates of thymocyte emigration in NOD recent thymic emigrants when compared with controls (9), indicating that other cell migrationrelated ligands and receptors might be also involved in driving NOD thymocyte migration.…”
mentioning
confidence: 99%
“…Furthermore, CXCL12 and CCR9 are considered as anti-apoptotic molecules (Geutskens et al, 2004) and interestingly, both molecules showed intense decrease here. Moreover, it is important to stress the close relation among hormones, diabetes and thymus.…”
Section: Discussionmentioning
confidence: 71%
“…Otherwise, in the alloxan-induced diabetes model we showed no alterations in fibronectin density and intense CXCL12 decrease but CXCR4 expression was not down regulated. The presence of CXCL12 secreted by TECs is fundamental for DN thymocyte migration from the cortical-medullar junction to the subcapsular region where these cells become DP and start CCR9 expression enabling them to migrate towards the medulla (Geutskens et al, 2004;Petrie and Zú ñ iga-Pflücker, 2007). In our model, both CCR9 and its ligand (CCL25) decreased and this fact may alter intrathymic migration and T cell maturation, leading as a consequence to a novel histological reorganization of thymus.…”
Section: Discussionmentioning
confidence: 99%
“…10,37 Cellular FN, which is mostly absent in normal adult tissues, is present in several matrices under tissue pathological conditions, including organ transplantation. 28 A role for FN-mediated leukocyte migration has been previously shown by others in skin inflammation, 39 rheumatoid arthritis, 40 diabetes 41,42 and by us in cardiac transplants. 8 Cellular FN is expressed by sinusoidal endothelial cells very early after liver injury.…”
Section: Discussionmentioning
confidence: 78%